Pseudoprogression after advanced first-line endocrine therapy in metastatic breast cancer with bone metastasis: A case report - Tian, Aijuan; Lv, Huiyun; Liu, Wei; Zhao, Jinbo; Zhao, Shanshan; Wang, Kainan; Song, Chen (Frontiers in Oncology, 2023)
Approximately 75% of patients with advanced breast cancer develop bone metastasis, which significantly affects both quality of life and survival of patients. Accurate determination of the status of bone metastases is important for developing treatment strategies and prognosis of the disease. Here, we report a case of a 33-year-old advanced metastatic breast cancer (MBC) patient with multiple bone metastases, in which advanced first-line endocrine therapy and second-line chemotherapy were both considered unsuccessful according to the efficacy evaluation by conventional imaging. Considering the possibility of bone pseudoprogression, the original endocrine scheme was reapplied, and bone metastases achieved a great response of non-complete response (CR) / non- progressive disease (PD). This case showed that in the course of therapy of the disease, if the bone scintigraphy (BS) shows increasing intensity in lesions or new lesions, which probably representing a favorable response (osteoblastic repair of osteolytic lesions ) to therapy,but not the worsening of metastatic lesions, called bone pseudoprogression. This paper will provide new insights into strategies for bone metastasis and shows the significance of distinguishing osteoblastic bone repair from real bone lesion progression in the clinical setting.